KAJIAN KRIMINOLOGIS TERJADI TINDAK PIDANA KORUPSI DANA DESA DI DESA PENAGA (Studi Desa Penaga Kabupaten Bintan Kepulauan Riau) - Heni Widiyani; Pery Rahendra Sucipta; Ahmad Ansyari Siregar; Ayu Efritadewi (Universitas Labuhanbatu, 2021)
Corruption that occurs in rural areas is very disturbing because it greatly affects the lives of rural communities, villages as the lowest government in the Indonesian state government structure are formed so that there is independence and progress and prevent the movement of people to cities. Corruption makes the infrastructure in the village not achieved according to the needs of the community. This juridical empirical research is to collect legal literature and compare the actual situation that occurs in the community by conducting interviews so as to find the facts and data needed, then the required data is collected, then the identification of the problem is carried out which ultimately comes to solving the problem . The people of the guardian village currently cannot enjoy the facilities that have been corrupted by the village head and the community economy poured out through BUMDES is not running properly due to the effects of corruption that occurred in 2017.Keywords : Corruption, Village Fund, Penaga Village